Prosthetic rehabilitation of a patient underwent hemimaxillectomy - János König; Tamás Déri; László Kádár; Péter Hermann (Hungarian Dental Association, 2023)
Two options are available for the treatment of oronasal or oroantral fistulas caused by traumatic or resective surgery: reconstructive surgery and reconstructive prosthetic care. However, the choice between these options is often controversial: it is not clear which treatment option would be the most effective for a given patient. The case presented in this article and the literature review in the field will be used to explore this issue.